Analysis of The Effectiveness of The Implementation of The Village Financial System Application (Siskeudes) in Buahdua District - Barokah, Dewi Laili Nur; Kartiwa, Aa; Kartika, Lilis (LPPM Universitas Sebelas April, 2024)
This study aims to assess the effectiveness of the Village Financial System Application (Siskeudes). The research was conducted in three villages: Sekarwangi, Cilangkap, and Panyindangan. This is a qualitative, descriptive study. Data collection methods included interviews, observations, and documentation, with primary data gathered through direct interviews with informants and secondary data consisting of documented information such as village history, location, organizational structure, and financial reports. The findings indicate that the implementation of the Siskeudes application in the three villages—Sekarwangi, Cilangkap, and Panyindangan in Buahdua District—has significantly aided and streamlined village financial management, proving effective overall. However, challenges remain, including version changes in the Siskeudes application, frequent errors during data entry, and a lack of human resources skilled in using the application.